2021
DOI: 10.3390/ijerph18115542
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and the Symptoms of PTSD in People with Depression and Anxiety Disorders during the COVID-19 Pandemic

Abstract: The purpose of this study was to examine the severity of post-traumatic stress disorder (PTSD) symptoms related to the COVID-19 pandemic in people with no diagnosis of mental illness, as well as in people who were diagnosed with depression or anxiety. Moreover, this study aimed to investigate the interplay between PTSD symptoms and self-assessed mental health associated with well-being. The 210 participants were divided into 3 groups: mentally healthy, participants with diagnosed depression, and participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Having a sense of control over the environment, a sense of directedness and intention, and the ability to regulate one's own behaviors (Ryff, 2014 ) may decrease avoidance among patients with PTSD. However, in a study conducted during the COVID‐19 pandemic among a sample of individuals with anxiety disorders, psychological well‐being was not related to any of the PTSD symptom clusters (Golińska et al., 2021 ); however, social well‐being was associated with hyperarousal and intrusions. Social well‐being may reflect aspects of the assumptive world, including the fundamental belief that the world is benevolent, which has been associated with intrusive cognitions (Freedle & Kashubeck‐West, 2021 ).…”
Section: Examining Well‐being In Posttraumatic Stress Disorder Treatm...mentioning
confidence: 98%
“…Having a sense of control over the environment, a sense of directedness and intention, and the ability to regulate one's own behaviors (Ryff, 2014 ) may decrease avoidance among patients with PTSD. However, in a study conducted during the COVID‐19 pandemic among a sample of individuals with anxiety disorders, psychological well‐being was not related to any of the PTSD symptom clusters (Golińska et al., 2021 ); however, social well‐being was associated with hyperarousal and intrusions. Social well‐being may reflect aspects of the assumptive world, including the fundamental belief that the world is benevolent, which has been associated with intrusive cognitions (Freedle & Kashubeck‐West, 2021 ).…”
Section: Examining Well‐being In Posttraumatic Stress Disorder Treatm...mentioning
confidence: 98%
“…Riad et al designed the COVID-19 Induced Anxiety Scale to evaluate the potential anxiety source in the general population, which could be utilized in the elderly population ( 20 ). In a study conducted in Poland, post-traumatic stress disorder (PTSD) symptoms related to COVID-19 worsened in both healthy people and patients diagnosed with depression and anxiety, and a lower emotional well-being was associated with a higher severity of PTSD ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first analyses concerning the mental state of Poles during the pandemic were performed in March (e.g., [5][6][7][8] and April 2020 (e.g., [9][10][11][12]). The research conducted in March [4] showed that, at first, Poles' emotional reactions were not dominated by negative emotions.…”
Section: Introductionmentioning
confidence: 99%